Circular Biogas-Based Economy in a Rural Agricultural Setting. (September 2017) - Blades, Luke; Morgan, Kevin; Douglas, Roy; Glover, Stephen; De Rosa, Mattia; Cromie, Thomas; Smyth, Beatrice
Abstract: This study investigates the application of a circular economy in a rural agricultural setting in Northern Ireland, centered around a typical anaerobic digestion (AD) plant, showing its potential to provide renewable energy for the electricity and transport fuel needs of an average dairy farm and associated milk processing facilities. It was calculated that a typical AD plant has the potential to fuel 22 average sized dairy farms in Northern Ireland, equating to the production, transport, and processing of 51, 986 litres of milk per day. The feedstock needs of the AD plant can be provided by the local farming community.